The Demand for Money: Preliminary Evidence from Industrial Countries - Kaufman, George G.; Latta, Cynthia M. (Journal of Financial and Quantitative Analysis, 1966)
During the past few years several money demand functions have been estimated for the United States. Although these functions may differ on the precise specification of the independent variables, most agree on their crude identity. Thus almost all functions include an income or wealth constraint and an interest rate price. Such functions have been applied exhaustively to data for various periods in United States history, both for the long run and for the short run. With few notable exceptions, the results differ more in degree than in substance. The quantity of money demanded is estimated to be a positive function of the constraint and a negative function of price. The studies have, however, overlooked an important body of possible collaborative evidence–that for other industrial countries. It may be reasonable to assume that the same basic forces underlie the demand for money in all industrial countries, it is of interest to contrast money demand functions for these countries with those obtained for the United States. This paper estimates demand functions for leading industrial countries and evaluates the results. No new theory is developed; rather, existing models are fitted to additional data to test their applicability to other countries.